PSYCHOMETRICAL CHARACTERISTICS OF RUSSIAN VERSIONS OF PEDSQL RHEUMATOLOGY MODULE AND PEDSQL GENERIC CORE SCALE QUESTIONNAIRES FOR THE ESTIMATION OF QUALITY OF LIFE OF CHILDREN AGED FROM 2 TO 4 YEARS OLD WITH JUVENILE RHEUMATOID ARTHRITIS - R.V. Denisova; V.Yu. Al'bitsky; E.I. Alexeeva; I.V. Vinyarskaya; S.I. Valieva; T.M. Bzarova; A.O. Lisitsin; E.Yu. Gudkova; K.B. Isaeva; A.M. Chomakhidze ("Paediatrician" Publishers LLC, 2008)
Quality of life is one of the principal criteria of efficacy of medical treatment of juvenile rheumatoid arthritis (JRA). There's no any questionnaire for the estimation of quality of life in children aged from 2 to 4 years old in Russia today. Questionnaire chaq (childhood health assessment questionnaire) can be useful for only estimation of functional status in children with JRA. A reliability, validity and sensitivity of Russian versions of ped SQL rheumatology module and ped SQL generic core scale questionnares for the estimation of quality of life in children aged from 2 to 4 years old with JRA are valued in this article. The value of chronbach's alpha was from 0,71 to 0,95, this is an evidence of reliability of Russian version of ped SQL questionnaire. Significant inverse negative relationship of quality of life rate and activity of disease and functional insufficiency index confirms validity of Russian versions of ped SQL questionnaires. Significant increase of quality of life rate in children with JRA aged from 2 to 4 years old treated with infliximab can confirm high sensitivity of Russian versions of ped SQL questionnaires. Authors made a conclusion that Russian versions of ped SQL questionnaires allow estimating quality of life in children with JRA aged from 2 to 4 years old. Key words: children, juvenile rheumatoid arthritis, quality of life, ped SQL rheumatology module, ped SQL generic core scale, infliximab.